Physical performance in female handball players according to playing position - Weber, J.; Wegner, M.; Wagner, H. (German Journal of Exercise and Sport Research, 2018)
Demands for female handball players are not yet sufficiently specified, especially not with respect to position-specific performance. For optimal match preparation, individual training based on specific demands of each position is necessary. Consequently, the aim of the study was to gain insight into position-specific differences in female handball players in order to establish position-specific training recommendations. Data from 652 female players from German leagues of all levels were analyzed using a test-battery assessing handball-relevant physical performance factors. Players were tested during their usual training in their regular training locations for running, throwing speed, jumping height, reaction-speed, basic running endurance, arm and abdominal muscle strength and hamstrings and lower back flexibility. Significant differences between positions were found for several parameters, while the differences were pronounced variably at the different performance levels. For example, goalkeepers performed worst in the Half-Cooper test (p<0.001) at elite level with wings displaying the best values. Halfbacks had the highest throwing speed (p<0.001) and jumping heights (p<0.002) at elite level. Goalkeepers were slowest for best and mean value out of five attempts (p<0.001; p<0.010) in 20m sprint but, together with wings outperformed half and centre backs at elite level in 30m sprint (best out of two attempts, p<0.001). Goalkeepers also did fewer chin ups than wing and back players at elite level (p<0.003). The present study demonstrated positional differences regarding physical performance parameters, thus suggesting the need to intensify position-specific training, especially for goalkeepers during preparation and in-season. Also, position-specific testing during selection-processes might be indicated.